Isolation and identification of lactobacillus sp. from Malaysian fermented food products using PCR method / Nurshyahira Madon - Madon, Nurshyahira (Faculty of Applied Sciences, 2016)
Studies have shown that there are lactic acid bacteria in market products especially dairy products. Recent studies showed that fermented food products also contain a variety of Lactobacillus sp. strains and they are found either naturally or synthetically. A total of four isolates of Lactobacillus sp. from Malaysian fermented food products, which are shrimp sauce, fish sauce, fermented durian and fermented tapioca, were identified by using molecular method which is the PCR method. The white colony formed on MRS agar was tested using PCR. By using primer Lacto-16S-F/Lacto-16S-R, specific for Lactobacillus sp. it showed that the four isolates are positive Lactobacillus sp. as they have similar molecular size with positive control which is 216 base pairs. The results also suggest that PCR is one of the molecular methods which are fast in identifying Lactobacillus sp. from Malaysian fermented food products.